The orb-weaving spider genus Eustala Simon, 1895 (Araneae, Araneidae): eight new species, redescriptions, and new records - Poeta, Maria Rita Muniz (Zootaxa, 2014)
Eight new species of Eustala Simon, 1895 are described from southern Brazil. Eustala guarani n. sp., from Paraná and E. catarina n. sp., from Santa Catarina, are based on males and females. Six species are described from Rio Grande do Sul: E. ericae n. sp., E. cidae n. sp., E. lisei n. sp., E. cuia n. sp., E. farroupilha n. sp., based on males and females, and E. eldorado n. sp., based only on males. Eustala mourei Mello-Leitão, 1947, from Paraná and E. ulecebrosa (Keyserling, 1892), described from Rio Grande do Sul are redescribed and illustrated. New records are given for Eustala albiventer (Keyserling, 1884), E. taquara (Keyserling, 1892), E. minuscula (Keyserling, 1892), E. itapocuensis Strand, 1916, E. photographica Mello-Leitão, 1944, E. levii Poeta, Marques & Buckup, 2010, and E. palmares, Poeta, Marques & Buckup, 2010. Eustala perfida Mello-Leitão, 1947, described from Paraná, and E. belissima Poeta, Marques & Buckup, 2010, from Rio Grande do Sul, are newly recorded from Uruguay. Distribution maps are provided.